2020
DOI: 10.1103/physrevlett.124.157701
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Enhancement in Graphene by in situ Reduction of Random Strain Fluctuations

Abstract: Microscopic corrugations are ubiquitous in graphene even when placed on atomically flat substrates. These result in random local strain fluctuations limiting the carrier mobility of high quality hBN-supported graphene devices. We present transport measurements in hBN-encapsulated devices where such strain fluctuations can be in situ reduced by increasing the average uniaxial strain. When ∼ 0.2% of uniaxial strain is applied to the graphene, an enhancement of the carrier mobility by ∼ 35% is observed while the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…The charge neutrality point (CNP) occurs at a positive gate voltage. From a linear fit near the CNP we find a field effect charge carrier mobility of ∼130 000 cm 2 V −1 s −1 , independent of ∆z, suggesting a high device quality and that random strain fluctuations are probably not dominating scattering processes here [33]. The additional conductance minimum at V g ≈ −1.2 V may originate from a large contact doping due to the overlap of the electrodes with the graphene region near the edge contacts [34], or from a super-superlattice effect in encapsulated graphene when both the top and the bottom hBN layers are aligned to the graphene lattice [35].…”
mentioning
confidence: 67%
“…The charge neutrality point (CNP) occurs at a positive gate voltage. From a linear fit near the CNP we find a field effect charge carrier mobility of ∼130 000 cm 2 V −1 s −1 , independent of ∆z, suggesting a high device quality and that random strain fluctuations are probably not dominating scattering processes here [33]. The additional conductance minimum at V g ≈ −1.2 V may originate from a large contact doping due to the overlap of the electrodes with the graphene region near the edge contacts [34], or from a super-superlattice effect in encapsulated graphene when both the top and the bottom hBN layers are aligned to the graphene lattice [35].…”
mentioning
confidence: 67%
“…Studying the magnetoelectric effect in sBLG experimentally requires two components: (1) a technique to strain dual-gated BLG devices with electrical contacts and (2) a technique to detect the resultant magnetization. Recently, several experimental approaches have been reported to continuously and reversibly strain devices based on two-dimensional materials while maintaining well-performing electrical contacts [10,[54][55][56]. In MoS 2 [9,10], the magnetization was probed previously using magneto-optic imaging, but due to the small bandgap in BLG this is challenging to apply here.…”
Section: B Proposed Experimental Observationmentioning
confidence: 99%
“…S1). A recent study demonstrated that ripples and corrugations can be present in hBN-supported graphene devices, leading to random strain fluctuations (18). Importantly, these can be reduced by uniaxially straining the device, thereby leading to a charge carrier mobility enhancement.…”
Section: Room-temperature Characterizationmentioning
confidence: 99%